Thermal conductivity and viscosity of deionised water and ethylene glycol-based nanofluids - Abdullah, Amirah; Mohamad, Imran Syakir; Bani Hashim, Ahmad Yusairi; Abdullah, Norli; Poh, Ban Wei; Md Isa, Mohamed Hafiz; Zainal Abidin, Syazwani (Universiti Malaysia Pahang, Malaysia, 2016)
This paper focused on thermal conductivity and viscosity of deionised water and ethylene glycol-based nanofluids at three different temperatures (6C, 25C and 40C). For the preparation of nanofluids, a two-step method, comprised of homogenisation and sonication, was used on a mixture of MWCNT-OH, PVP and the base fluid. The results revealed that thermal conductivity was enhanced by about 8.86% for 0.8 wt% deionised water-based MWCNT-OH nanofluid, and by 5.37% for 0.2 wt% ethylene glycol-based MWCNT-OH nanofluid. Meanwhile, in viscosity test, the highest temperature of 40C exhibited lowest viscosity. This phenomenon happened only with ethylene glycol-based nanofluid, whilst the data on the viscosity of deionised water-based nanofluid was inconsistent at certain nanofluid concentrations . In conclusion, addition of MWCNT-OH into base fluid enhanced base fluid performance , giving it the potential to be used in cooling system applications. Keywords: Nanofluids; thermal conductivity; viscosity.